Cyber attacks and their impacts on the shipping industry. Identify the risks and suggest ways to mitigate. (maritime services) - Poh, Sze Ping (Nanyang Technological University, 2021)
Today, the traditional shipping industry has been slowly adopting and integrating technologically – enabled solutions into their system of work, such as the use of Blockchain, Automation and Information Technology within the various sectors. With these technologies being put in-place, sectors like the maritime services have been able to achieve higher efficiency and effectiveness in performing operational activities such as streamlining of supply chain processes through the use of e – B/L, container tracking system, vendor managed system and automation. However, the employment of technologies within the operational activities also increases their risk to potential cyber-attacks. Moreover, there has been a lack of focus on the danger of adopting technologies compared to the benefit it can bring along. As quoted “It takes 20 years to build a reputation and few minutes of cyber-incident to ruin it.” by Stephane Nappo (Vice President Global Chief Information Security Officer), the danger of technology can only be secured with proper cyber security measures in-place. Hence, this paper aims to increase the maritime services sector’s awareness on cyber-attacks through the discussion of the potential impacts from the commonly used technologically – enabled solutions. Following, an analysis based on information and current industry practices will be obtained through qualitative and quantitative research, to measure the level of risk exposed to the maritime services sectors. Lastly, with reference to the level of risk subjected by the sector, mitigation solutions will be proposed. The mitigation solutions are addressed from 3 levels – individual, corporate, and global so as to provide a more comprehensive suggestions for industry players to adopt.